2003
DOI: 10.1074/jbc.m305210200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of a Novel, Inactive, Lysine 49 PLA2 from Agkistrodon acutus Venom

Abstract: The crystal structure of acutohaemolysin, a lysine 49 phospholipase A2 protein with 1010 non-hydrogen protein atoms and 232 water molecules, has been determined ab initio using the program SnB at an ultrahigh resolution of 0.8 Å. The lack of catalytic activity appears to be related to the presence of Phe 102 , which prevents the access of substrate to the active site. The substitution of tryptophan for leucine at residue 10 interferes with dimer formation and may be responsible for the additional loss of hemol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
1
30
0
1
Order By: Relevance
“…The existence of a consensus sequence Tyr 25 -Gly-Cys-Asn-Cys-Gly-X-X-X-Arg-Gly 35 implies that this region is functionally homologous among all family members. Compared with the neighboring region containing Cys 27 -Asn-CysGly 30 , the electron density of Val 31 -Gly-Gly 33 is quite poor, indicating that these residues have relatively high thermal motion [56]. In connection with the Asp 49 PLA 2 activity, Scott et al [57] proposed that the backbone amide of Gly 30 stabilizes the oxyanion of the substrate tetrahedral intermediate.…”
Section: A Calcium-binding Loopmentioning
confidence: 98%
See 2 more Smart Citations
“…The existence of a consensus sequence Tyr 25 -Gly-Cys-Asn-Cys-Gly-X-X-X-Arg-Gly 35 implies that this region is functionally homologous among all family members. Compared with the neighboring region containing Cys 27 -Asn-CysGly 30 , the electron density of Val 31 -Gly-Gly 33 is quite poor, indicating that these residues have relatively high thermal motion [56]. In connection with the Asp 49 PLA 2 activity, Scott et al [57] proposed that the backbone amide of Gly 30 stabilizes the oxyanion of the substrate tetrahedral intermediate.…”
Section: A Calcium-binding Loopmentioning
confidence: 98%
“…They cause plasma membrane perturbation that promotes a heavily increase of the cytosolic Ca 2+ concentration leading to cell degeneration of muscle cells and neuromuscular junction [140]. PLA 2 s employ a conserved catalytic triad consisting of His 48 , Tyr 52 , and Asp 99 to hydrolyze substrate into free fatty acids and lysophospholipids [56]. It is believed that His 48 and Asp 99 are involved in the nucleophilic attack of a water molecule at the sn-2 position of the phospholipid substrate.…”
Section: B Catalytic Site and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This study has demonstrated the feasibility of the method and was discussed in Part I. The structures of trypsin [36] and of a snake venom phospholipase [37], both at 0.8 Å resolution, were also analyzed recently using the program MoPro; they display clear bonding electron density.…”
Section: Protein Charge Density Refinementmentioning
confidence: 99%
“…Previously, refinement at subatomic resolution using multipolar models has been reported for crambin (Fernandez-Serra et al, 2000;0.54 Å), trypsin (Schmidt et al, 2003; 0.80 Å), phospholipase (Liu et al, 2003; 0.80 Å; for the resolution higher than 0.86 Å the data completeness is below 50%) and scorpion toxin (Housset et al, 2000;0.96 Å). The corresponding models were extracted from the PDB (Bernstein et al, 1977;Berman et al, 2000).…”
Section: Comparative Refinement At Subatomic Resolutionmentioning
confidence: 99%